2001
DOI: 10.1063/1.1409564
|View full text |Cite
|
Sign up to set email alerts
|

Electric measurements with constant current: A practical method for characterizing dielectric films

Abstract: This article assesses the use of the constant current ͑CC͒ method for characterizing dielectric films. The method is based on charging the sample with a constant current ͑current stress͒ and measuring the corresponding voltage rise under the closed circuit condition. Our article shows that the CC method is an alternative to the constant voltage stressing method to study the electric properties of nonpolar, ferroelectric, and polar polymers. The method was tested by determining the dielectric constant of polyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The molecules were able to do a complete orientation at low frequency but they were not able to achieve the same orientation at high frequency [ 49 ]. However, the ε ″ of the PTFE sample did not change with frequency because PTFE is a nonpolar polymer [ 50 ], which means its complex permittivity is not dependent on frequency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecules were able to do a complete orientation at low frequency but they were not able to achieve the same orientation at high frequency [ 49 ]. However, the ε ″ of the PTFE sample did not change with frequency because PTFE is a nonpolar polymer [ 50 ], which means its complex permittivity is not dependent on frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The molecules were able to do a complete orientation at low frequency but they were not able to achieve the same orientation at high frequency [49]. However, the ε of the PTFE sample did not change with frequency because PTFE is a nonpolar polymer [50], which means its complex permittivity is not dependent on frequency. The increment in complex permittivity with increasing rFe2O3 nanofiller can be attributed to the polarization process due to the enhanced conductivity and interfacial polarization in the composite and hopping exchange of charges between localized states [23].…”
Section: Complex Permittivity Of Rfe 2 O 3 -Ptfe Nanocompositesmentioning
confidence: 98%
“…The procedure followed is acceptable since it has been shown that changing the controlling variable has no great effect on the shape of the hysteresis loops. 28 …”
Section: Experimental Details and Materialsmentioning
confidence: 99%
“…It can be observed from the Figure 6 that the values of ε ′ and ε ″ were low for the samples with a lower content of recycled Fe 2 O 3 nano‐powder. PTFE is a nonpolar polymer, [ 44 ] which means that its dielectric constant does not depend on frequency as electronic polarization is instantaneous regardless of frequency. The complex permittivity of PTFE was 2.01 − j * 0.008 throughout the whole range of frequency which agreed with an earlier study.…”
Section: Resultsmentioning
confidence: 99%